Strategi Komunikasi Sanggar Seni Tari Ridwan CS dalam Membangun Kepercayaan Orang Tua Siswa - Ahmad Agus Salim (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
In this era of globalization, challenges arise for art practitioners and art studios in preserving traditional arts. This phenomenon creates significant obstacles for traditional art studios, particularly dance studios, in attracting the interest of younger generations and building trust among parents to encourage their children's participation. This study aims to analyze the communication strategies implemented by the Ridwan CS Dance Studio in building trust among students' parents. The research adopts Ronald D. Smith's (2017) Public Relations strategic planning model from his book Strategic Planning for Public Relations, which outlines four stages of strategic planning divided into nine steps. The results indicate that the communication strategies employed by the studio have been quite effective in establishing trust among parents. This conclusion is supported by findings showing that students receive parental support to learn at the Ridwan CS Dance Studio. Additionally, parents have provided feedback indicating that they feel reassured about their children's involvement and learning activities at the studio.4o